ALGEBRAIC IDENTITIES
Let us recall the following algebraic identities is earlier.
(a + b)2 = a2 + 2ab + b2. (a – b)2 = a2 – 2ab + b2. (a + b) (a – b) = a2 – b2. (x + a) (x + b) = x2 + (a + b) x + ab
Ex. Expand each of the following :
(i) (2x + 3y)2
(ii) (4x – 5y)2
(iii) (x + 5) (x + 6)
(iv) (x – 3) (x – 5)
Sol. (i) (2x + 3y)2.= (2x)2 + 2.2x.3y + (3y)2 b [∵ (a + b)2 = a2 + 2ab + b2]
= 4x2 + 12xy + 9y2
(ii) (4x – 5y)2 = (4x)2 + 2.4x.5y + (5y)2 [∵ (a – b)2 = a2– 2ab + b2]
= 16x2 – 40xy + 25y2
(iii) (x + 5) (x + 6) = x2 + (5 + 6)x + 5.6 [∵ (x + a) (x + b) = x2 + (a + b) x + ab]
= x2 + 11x + 30
(iv) (x – 3) (x – 5) = {x + (–3)} {x + (–5)} [∵ (x + a) (x + b) = x2 + (a + b) x + ab]
= x2 + {(–3) + (–5)}x + (–3).(–5) = x2 + (–3 – 5)x + 15. = x2 – 8x + 15
Ex. Find the product using appropriate identities :
(i) (x + 8) (x + 8)
(ii) (3x – 2y) (3x – 2y)
(iii) (x + 0.1) (x – 0.1)
Sol. (i) (x + 8) (x + 8) = (x + 8)2. = x2+ 2(x) × 8 + (8)2 = x2 + 16x + 64.
(ii) (3x – 2y) (3x – 2y) = (3x – 2y)2 [∵ (a – b)2 = a2 – 2ab + b2]
= (3x)2 – 2(3x) × 2y + (2y)2. = 9x2 – 12xy + 4y2.
(iii) (x + 0.1) (x – 0.1) = (x)2 – (0.1)2 [∵ (a + b) (a – b) = a2 – b2]
= (x)2 – 0.01
No comments:
Post a Comment